Մանայի թագավորության վարչաքաղաքական միավորների և դրանց տեղադրության շուրջ - Գրեկյան, Երվանդ («Զանգակ - 97»)
The problem of historical geography and administrative division of ancient Oriental kingdom of Manna is still actual. The number of administrative-political units of Manna, known from cuneiform sources, reachs up to thirteen, including eight districts and five "lands".
Keywords: Պատմություն; Քաղաքականություն